Morphological and Biochemical Diversity of Shallot Landraces Preserved Along the Croatian Coast - Major, Nikola; Goreta Ban, Smiljana; Urlić, Branimir; Ban, Dean; Dumičić, Gvozden; Perković, Josipa (Frontiers in Plant Science, 2018)
Shallots are a valuable minor Allium crop, and are propagated vegetatively and maintained in home gardens across generations along the Croatian coast and island areas. Shallot landraces growing along the Croatian coast fall into three genotypes: Allium cepa Aggregatum group (2n = 2x = 16), A. × proliferum (Moench) Schard. (2n = 2x = 16), and A. × cornutum Clementi ex Vis. (2n = 3x = 24), among which A. × cornutum is the most widespread. The aim of this study was to differentiate shallot accessions collected from local farmers using morphological markers. Also, the chemical composition including phenolic content, phenolic profile, total antioxidant capacity, and mineral composition, of shallot accessions was compared with that of the local landraces of common onion, and with market available shallot and common onion cultivars. Based on morphological observations and using multivariate classification, shallot landraces were classified into three distinct groups. Properties, based on which A. × cornutum can be differentiated from A. cepa Aggregatum and A. × proliferum, are stamen morphology, stamen length, leaf and scape vegetative properties, number of bulbs in cluster, cluster mass, and bulb diameter. Flower diameter and flower pedicel length differentiate A. × cornutum and A. × proliferum from A. cepa Aggregatum. Significant variability was observed in the biochemical profiles across tested accessions. Compared with the commercial common onion cultivars, local shallot accessions have higher bulb N, P, and K content. The major phenolic compounds identified in shallots were quercetin-4′-glucoside and quercetin-3,4′-diglucoside. Additionally, several other minor phenolic compounds were also identified. Morphological and biochemical profiles were evaluated using Partial Least Square (PLS) analysis. Specific morphological traits and biochemical markers for possible species identification are proposed.